1993
DOI: 10.1021/jm00073a022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in vitro binding profile, and autoradiographic analysis of [3H]-cis-3-[(2-methoxybenzyl)amino]-2-phenylpiperidine, a highly potent and selective nonpeptide substance P receptor antagonist radioligand

Abstract: The synthesis of a highly potent and selective NK1 receptor antagonist radioligand, [3H]-cis-3-[(2-methoxybenzyl)amino]-2-phenylpiperidine (6a) is described. The in vitro binding pharmacology and autoradiographic distribution of 6a in guinea pig brain following peripheral administration are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…2 were kindly donated. CP96,345 and CP99,994 were provided by Dr. John A. Lowe III (Pfizer, Groton, CT) (Snider et al, 1991;Rosen et al, 1993). CGP49,823 was provided by Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 were kindly donated. CP96,345 and CP99,994 were provided by Dr. John A. Lowe III (Pfizer, Groton, CT) (Snider et al, 1991;Rosen et al, 1993). CGP49,823 was provided by Fig.…”
Section: Methodsmentioning
confidence: 99%
“…All mutations were verified by restriction endonucle- Bold, four amino acid residues common to all four tachykinin peptides. The lead compounds for the nonpeptide antagonists CP96,345 (Snider et al, 1991), CP99,994 (Rosen et al, 1993), RP67,580 (Garret et al, 1991), RPR100,893 (Tabert and Peyronel, 1994), LY303,870 (Gitter et al, 1995), and SR140,333 (Emonds-Alt et al, 1993b) were found by screening of chemical files, whereas the initial lead compounds for CGP49,823 (Schilling et al, 1993), CAM4092 (Boyle et al, 1994), and FK888 (Fujii et al, 1992) were peptide-based compounds.…”
Section: Methodsmentioning
confidence: 99%
“…The pseudo‐enantiomeric catalyst 73 (derived from quinidine) produced ent ‐ 68a with comparable enantioselectivity. Enantiopure ent ‐ 68a can be transformed into unsaturated piperidine 74 and bicycle 75 , which are advanced intermediates in the synthesis of drugs candidates such as (+)‐CP‐99,994, (+)‐CP‐113,054, and (+)‐L‐733,060 (Scheme ) ,, . Additionally, through a 1,2‐aryl shift mediated by silver trifluoroacetate, piperidine 68d could be converted into 70 while preserving the ee .…”
Section: Thiocarbamate and Carbamate Catalystsmentioning
confidence: 99%
“…For example, the piperidine alkaloid pseudodistomin A 1 , which was isolated from tunicates, exhibits calmodulin antagonistic activity, and therefore strongly depresses tumor growth in vitro . The racemic compound CP-99,994 2 was recently discovered as the most potent antagonist of substance P, an undecapeptide, which acts as a neurotransmitter in the central and peripheral nervous system and is involved in smooth muscle contraction and regulation of immune responses we were interested in whether this reaction type could be extended to the syntheses of 2,3,4-trisubstituted piperidines 3 bearing an amino group at C-3 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%